A Strange, Sad Comedy - Seawell, Molly Elliot, 1860-1916 (Salt Lake City, UT : Project Gutenberg, 2022)
"A Strange, Sad Comedy" by Molly Elliot Seawell is a novel written in the late 19th century. Set during the American Civil War, it revolves around Colonel Archibald Corbin and his family at Corbin Hall in Virginia, showcasing their genteel lifestyle amidst the chaos of the war. The main character, Colonel Corbin, is portrayed as a dignified gentleman trying to navigate the adversities of the war while retaining his composure and sense of honor. The opening of the novel introduces Colonel Corbin as he reads in his library, reflecting on the changes brought by the war. As federal soldiers arrive at his home, the Colonel exhibits a serene determination to uphold his dignity in the face of losing his property. Shortly after the soldiers depart, the narrative shifts to a visit from Sir Archibald Corbin, a young Englishman seemingly related to the Colonel, which opens up themes of family and generational ties. The initial interactions both highlight the Colonel's calm demeanor and hint at the underlying tensions of life during wartime, setting the stage for a mix of comedy and pathos as the story unfolds. (This is an automatically generated summary.)
Release date is 2022-03-20
D A Alexander, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: United States -- History -- Civil War, 1861-1865 -- Fiction; Virginia -- Fiction; Newport (R.I.) -- Fiction; United States -- Social life and customs -- 1865-1918 -- Fiction